Roots of lyric : primitive poetry and modern poetics - Welsh, Andrew, 1937- (Princeton University Press, 2019)
Folk riddles, emblems, charms, and chants are a few of the traditional forms examined by Andrew Welsh to discover the means by which poetic language achieves its powerful effects. His book shows how the roots of lyric are embodied in primitive verse forms, how they are raised to higher powers in poetry from the Renaissance to the twentieth century, and how an awareness of them can illuminate our reading of the poetry of any age. Andrew Welsh is Associate Professor of English at Rutgers University. Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.